Insuficiencia de la norma que regula la terminación de las uniones de hecho dentro del codigo civil - Yepez Wilchez, Sandra Ivanova (2015)
As a graduate of the School of Law at the Distance Learning mode and committed to the legal development, Social and Administrative Law of the National University of Loja; and concerned about the obsolescence of the rule in particular those governing the termination of de facto unions in the Civil Code, I proceeded to develop the research work entitled "FAILURE OF POLICY GOVERNING THE TERMINATION OF THE MEETING MADE WITHIN CIVIL CODE ", in which I show the problems arising from legal gap in the Ecuadorian Civil Code, by failing to determine explicitly grounds for termination of de facto union, as being considered as a form of family integration equal families formed by marriage, must be set the same grounds for termination of marriage. The problem posed to research is very important and has legal significance, because we live it every day and that is framed within the problematic of Legal Science in the Civil Law. This legal issue is a social reality that affects all people in general, because the current lack of regulation causes for the termination of the Union Fact that go hand in hand with those established for the termination of marriage, does not allow the will of the cohabitants run, which affects not only a person or group, but to the Ecuadorian social cluster and thus avoid discrimination and legal and social recognition. The research report is structured according to the provisions of Article 144 of the Rules of Academic System of the National University of Loja; and is broken down as follows: Introductory Section, which consists of the Home, Certification of Thesis Director, Authorship, Dedication, Acknowledgements and Table of Contents; Introductory Section, the topic is the title and name of the author, a summary Castilian and translated into English-Abstract, Introduction; Body of the Final Report, which contains: Literature Review, which should be reviewed everything related to the Framework, Marco Doctrinal and Legal Framework; Materials and Methods that relates to the methodology used, procedures performed to obtain the information; Results of Surveys; Discussion in this part of the report verifying the objectives is performed, the proposed legal reform is based; Synthesis is the penultimate part and relate the findings, recommendations and the proposed Law Reform as References have latter part that relates to the literature used throughout the research process, the rate of all research and then annexes.